Interlaminar reinforcement for enhancing low-velocity impact response of woven composites. Issue 15 (August 2018) - Castellanos, AG; Islam, Md S; Tarango, E; Lin, Y; Prabhakar, P
This paper proposes a novel technique for improving the low-velocity impact response of woven composites, which involves synthesizing ZnO nanowires on dry woven carbon fabric layers. ZnO nanowire reinforcements were added to the interlaminar regions that are most susceptible to damage within layered composites, which were determined using finite element method analysis. Upon fabricating the laminates with and without ZnO nanowire interlaminar reinforcements, low-velocity impact responses were investigated next and the degree of damage was experimentally determined. The physical tests reveal that the samples with ZnO nanowires experience a lower degree of damage, up to a maximum of 25% for different impact energies, in comparison to the samples without ZnO nanowires. Therefore, the study presented in this paper shows the potential of using ZnO nanowires as interlaminar reinforcements for woven composites to improve their impact damage resistance.